1989
DOI: 10.5271/sjweh.1886
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks among New Zealand meat workers.

Abstract: . Ca ncer risks among New Zealand meat wor kers. Scand J Work Environ Health 1989;15:24-29. The study reports a series of case-referent studies based on the New Zealand Ca ncer Register and involving 19904 male cancer patients aged 20 years or more at the time of registr ation during the period 1980-1984. For each cancer site, the registration s for the remaining sites form ed the referen ce group. An increase d risk for lung (O R 1.30,95 % CI 1.06-1.58) a nd laryngeal (OR 2.01, 95 % CI 1.19-3.39) cancer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
(42 reference statements)
4
24
0
Order By: Relevance
“…James reported an in creased mortality from prostate cancer among meat workers [22]. In other studies, however, no excess risk was found for these occupations [19,21,23,24]. In one earlier study a significantly elevated risk for stock clerks and storekeepers was found [25].…”
Section: Discussionmentioning
confidence: 99%
“…James reported an in creased mortality from prostate cancer among meat workers [22]. In other studies, however, no excess risk was found for these occupations [19,21,23,24]. In one earlier study a significantly elevated risk for stock clerks and storekeepers was found [25].…”
Section: Discussionmentioning
confidence: 99%
“…Gustavsson et al (13) found an OR of 0.9 for men who had worked with meat packing. Reif et a1 (14) found that only a minority of workers were exposed to PVC decomposition products. This finding is consistent with the work conditions reported for Danish and Swedish butchers.…”
Section: Which Exposures In the Work Environment Could Possibly Explamentioning
confidence: 99%
“…Reif et al (14) controlled indirectly for tobacco smoking with data from a national survey which showed the number of current smokers among food and beverage workers to be 47% compared with 38% on the average among employed men. Assuming slaughterhouse workers to have the same smoking habits as workers in the food and beverage industry, Reif et al expected an RR of 1.20 due to smoking alone.…”
Section: Is the Excess Risk Possibly Caused By Exposures In The Work mentioning
confidence: 99%
See 2 more Smart Citations